Controlled 3D co-culture of beta cells and endothelial cells in a micropatterned collagen sheet for reproducible construction of an improved pancreatic pseudo-tissue - Haewon Seo; Jaejung Son; Je-Kyun Park (APL Bioengineering, 2020)
The co-culture of beta cells and endothelial cells in constructing a pancreatic pseudo-tissue can provide a functional advancement for in vitro diabetic-related drug testing and biological studies or in vivo transplantation. In order to mimic the pancreatic tissue more similar to in vivo, it is necessary to control the microenvironment, including cell–cell and cell–extracellular matrix interactions. In this study, we report a geometrically controlled three-dimensional (3D) pancreatic model where MIN6 and MS1 cells are co-cultured within a micropatterned collagen sheet. In 4–10 days, depending on the cell seeding concentration, the MIN6 cells formed islet-like clusters surrounded by an endothelial MS1 cell monolayer. The MS1 cells also formed monolayers at the edge of the micropatterns connecting between the clusters, resulting in a blood vessel-like structure in which no cells were found. It was confirmed that the 3D co-culture structure was not formed in a non-patterned sheet and the structure also helped insulin secretion of MIN6 cells. By simply embedding the cell mixture and the hexagonal micropattern into the collagen sheet, we were also able to achieve the highly reproducible fabrication of a 3D pancreatic pseudo-tissue construct for in vivo and in vitro applications.